PERAN PRODUSER DALAM PEMBUATAN FILM PENDEK “GAGAL PAHAM” - Sarah Sausan Abani; Arryadianta (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Film is a combination of visual elements from various forms of art such as music, visual arts, and sound art, brought together by technological advancements. Aside from serving as a tool to express events, films are also used as an effective communication medium for audiences. There are various types of films, one of which is short film. A short film is a concise presentation with a short duration, yet it possesses a distinctive and complex atmosphere that captivates the audience. The work intended for this final project is a short film titled "Gagal Paham." The short film "Gagal Paham" narrates the occurrence of a misunderstanding between a mother and her son. Crafted to engage the audience, complex issues unfold within the storyline. This film itself is inspired by Ernest Prakasa's work titled "Susah Sinyal." Adopting the drama and family genres, this film is created with a duration of approximately 20 minutes. The genre of this work is also familiar with everyday occurrences, making it easily comprehensible for the audience. In this final project, it is collaborated on by three students, each with different tasks and responsibilities. The writer within the project team acts as the producer, primarily responsible for cost planning, scheduling activities, and more, to ensure a smooth and successful film production process